Electronic and Optical Excitations at the Pyridine/ZnO(101¯0) Hybrid Interface. Issue 2 (24th October 2018) - Turkina, Olga; Nabok, Dmitrii; Gulans, Andris; Cocchi, Caterina; Draxl, Claudia
Abstract: By combining all‐electron density‐functional theory with many‐body perturbation theory, a prototypical inorganic/organic hybrid system, composed of pyridine molecules that are chemisorbed on the nonpolar ZnO( 10 1 ¯ 0 ) surface is investigated. The G 0 W 0 approximation is employed to describe its one‐particle excitations in terms of the quasiparticle band structure, and the Bethe–Salpeter equation is solved to obtain the absorption spectrum. The different character of the constituents leads to very diverse self‐energy corrections of individual Kohn–Sham states, and thus the G 0 W 0 band structure is distinctively different from its DFT counterpart, that is, many‐body effects cannot be regarded as a rigid shift of the conduction bands. The nature of the optical excitations at the interface over a wide energy range is explored and it is shown that various kinds of electron‐hole pairs are formed, comprising hybrid excitons and (hybrid) charge‐transfer excitations. The absorption onset is characterized by a strongly bound bright ZnO‐dominated hybrid exciton. For the selected examples of either exciton type, the individual contributions from the valence and conduction bands are analyzed and the binding strength and extension of the electron‐hole wavefunctions are discussed. Abstract : The electronic and optical excitations of the inorganic/organic hybrid interface, pyridine/ZnO( 10 1 ¯ 0 ), are investigated by state‐of‐the‐art first principles approaches. A type‐I level alignment and intense light absorption are found in the visible region, with the onset characterized by a strongly bound bright ZnO‐dominated hybrid exciton. Over a wide energy range, hybrid and (hybrid) charge‐transfer excitons are formed.